Tips for single‐port laparoscopic cholecystectomy. (15th April 2014) - Kameyama, Noriaki; Miyata, Ryohei; Tomita, Masato; Mitsuhashi, Hiroaki; Baba, Shigeaki; Imai, Shunichi
Abstract Single‐port laparoscopic cholecystectomy (SPLC) is an emerging technique and gaining increased attention by its superiority in cosmesis. A 1.5‐cm vertical transumbilical incision is used for the single port, followed by the glove method. Indications for SPLC are the same as those for standard 4‐port laparoscopic cholecystectomy, including patients with morbid obesity, previous upper abdominal surgery, severe acute cholecystitis, or suspected presence of common bile duct stones. Some randomized controlled trials have shown negative results of SPLC regarding operative time, wound‐related complications, and postoperative pain. However, our retrospective analysis shows equivalent clinical outcomes among the two approaches in terms of postoperative pain and complications. In this context, SPLC can be a good option for gallbladder pathologies.